Treatment of Textile Industrial Wastewater using Membrane Technology: A Review - Amillia Amillia; Maryudi Maryudi; Firda Mahira Alfiata Chusna; Dhias Cahya Hakika; Aster Rahayu; Imam Santosa; Hamad Khudhair Mohammed (Universitas PGRI Madiun, 2024)
Textile industry wastewater is a very complex pollutant-containing waste with high dye intensity, requiring proper and appropriate treatment. Membrane technology is one of the appropriate methods for treating textile wastewater due to several advantages such as environmentally friendly and biopolymer-based processing. Therefore, this review aimed to determine the effectiveness of membrane technology and provide information regarding the appropriate treatment of textile wastewater. The articles subjected to review were obtained from several journal sources such as ScienceDirect, Elsevier, Springer, Google Scholar, and national journals. The results showed that several membranes had been used in textile wastewater treatment, such as PTFE (Polytetrafluoroethylene), PES (Polyethersulfone), Polysulfone-Polyvinyl Pyrrolidone Blend Polymer Composite Membrane, CA (Cellulose Acetate), Cellulose Membrane of Sargassum Sp., polysulfone (PSF), Bacterial Cellulose Membrane, and cellulose acetate propionate (CAP). Furthermore, membrane technology was found to reduce dye pollutants in textile wastewater with the highest coefficient value of approximately 97%.